Fixed-Time Connectivity Preserving Tracking Consensus of Multiagent Systems with Disturbances. (21st February 2020) - Sun, Fenglan; Liu, Peiyong; Kurths, Jürgen; Zhu, Wei
Abstract : This text studies the fixed-time tracking consensus for nonlinear multiagent systems with disturbances. To make the fixed-time tracking consensus, the distributed control protocol based on the integral sliding mode control is proposed; meanwhile, the adjacent followers can be maintained in a limited sensing range. By using the nonsmooth analysis method, sufficient conditions for the fixed-time consensus together with the upper and lower bounds of convergence time are obtained. An example is given to illustrate the potential correctness of the main results.